Effect of Single Clove Garlic Extract (Allium Sativum Linn) on Blood Sugar Levels, Malondialdehyde, Insulin Levels and Insulin Resistance (Experiments in Rats (Rattus Novergicus) Induced by Streptozotocin - Yeni Susanti; Merryana Adriani; Annis Catur Adi (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Oral antidiabetic drugs mostly give unwanted side effects, so it is necessary to develop a traditional treatment system for diabetes mellitus which is relatively safe. The purpose of this study was to determine the effect of single clove garlic on decreasing blood sugar levels, decreasing malondialdehyde levels, increasing insulin levels, and decreasing insulin resistance in experimental rats induced by streptozotocin 50 mg / KgBB. (P1) therapy of single clove garlic 50 mg/kgBB, (P2) therapy of single clove of garlic 75 mg/KgBB, (P3) therapy of single clove of garlic 125 mg/KgBB. The most effective dose in this study was 125 mg/KgBB. Comparison test the mean of each group with the Manova test. The flavonoids in single clove garlic have been shown to be powerful agents to reduce the pathogenesis of diabetes and its complications.